Comparative Analysis of Debt Restructuring Strategies in Developing Economies: A Case Study of Ghana, Zambia, and Sri Lanka - Abeyrathne, Dilmini Hasintha; Kamburawala, Tharindu Udayanga (HAPSc Policy Briefs Series, 2023)
The issue of global debt distress is a matter of great concern, not just for the affected developing countries but also for developed countries and international organisations. According to the United Nations Development Program (2022), 54 developing economies are currently grappling with severe debt problems. During the period of 2020 to 2022 Ghana, Zambia, and Sri Lanka, representing the African and Asian regions, have found themselves in dire financial straits. This study aims to discover the common and specific reasons that led to the mounting debt crises in these three countries. The study describes the tax revenue challenges and governance issues, middle income trap and China’s role in debt restructuring discussions as common challenges apart from country specific challenges. Timely discussions with the International Monetary Fund (IMF) and expedited agreements with creditors, and updated debt restructuring mechanisms are drawn to attention in this study.